2018
DOI: 10.2478/prilozi-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Hemispheric EEG Coherence Study in Adults with Neuropsychiatric Disorders

Abstract: Functional connectivity between different regions of the brain in the resting state has been a recent topic of interest in neurophysiological research. EEG coherence happened to be an useful tool for measuring changes in neuro-psycho-physiological functioning which are not detectable by simply measuring amplitude or power spectra. The aim of our study was to investigate the changes in the EEG coherence in groups of different mental disorders such as: depression, general anxiety disorder, ADHD, Asperger syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…This characteristic was particularly noticeable in the positive valence group. Delta coherence increases with cognitive load [79] and reflects the emotion regulation process [34]; this characteristic of delta connectivity may be relevant to changes in emotion. In addition, in line with our results, there is a positive correlation between valence and frontal inter-hemispheric flow [80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic was particularly noticeable in the positive valence group. Delta coherence increases with cognitive load [79] and reflects the emotion regulation process [34]; this characteristic of delta connectivity may be relevant to changes in emotion. In addition, in line with our results, there is a positive correlation between valence and frontal inter-hemispheric flow [80].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these sounds are expected to elicit positive emotions [33], but we expected that they would elicit different emotions. Delta and alpha bands play an important role in the emotion regulation process [15], [34]. In this regard, we hypothesized that the brain signals may differ with subjective emotions, especially in delta and alpha bands, even if participants listened to the same auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…To rectify this, we examined auditory and visual evoked signals across the five EEG frequency bands. The key results from the spatial coherence analysis, a measure of synchronization of the electro-cortical activities (Markovska-Simoska, et al, 2018), revealed that migraineurs showed significantly lower spatial coherence of alpha-band neural activities during the auditory and visual stimuli in comparison with the controls. This profile was especially evident in lower to mid-range distances (not too large, not too short) between the frontal clusters of scalp electrodes and other clusters especially during the visual stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although EEG amplitude measurements or calculation of power spectra are simple to compute, we elected to study coherence, which is considered to be a reliable measure of synchronization of the electro-cortical activities (Markovska-Simoska, et al, 2018) and has been used to investigate connectivity in migraine previously (refs where applicable). Because spatial coherence drops as a function of distance between electrodes, we analyzed the estimated coherence as a function of inter-electrode distance (link length).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research we evaluated inter and intrahemispheric EEG coherence in different psychiatric disorders such as: ADHD, anxiety, depression, and Asperger's syndrome (ASP) compared with healthy controls [14].…”
Section: Analysis Of Eeg Characteristics and Coherence In Patients DImentioning
confidence: 99%